Caracterização dos pacientes oncológicos-hematológicos internados com neutropenia febril pós quimioterapia em um hospital terciário - Horner, Christine (2023)
Hematological malignancies are part of a heterogeneous group of malignancies that are responsible for significant mortality rates. The major concern in onco-hematological patients with leukopenia is febrile neutropenia (NF), which is a medical emergency as it carries a risk of progression to fulminant sepsis. Febrile neutropenia is a febrile syndrome associated with a reduction in the number of neutrophils, being a frequent complication of systemic cancer treatment, with a prevalence that can reach up to 40%. Defined by the presence of severe neutropenia associated with fever, commonly occurring at the nadir of a chemotherapy cycle, fever during chemotherapy-induced NF may be the first and only indication of a serious infection The criterion for diagnosing febrile neutropenia is an absolute count neutrophil count < 500 /mm3 associated with peak fever > 38.3°C or temperature > 38°C for one hour. But there is no consensus and we can find another criterion: > 38.5ºC or three peaks ≥ 38ºC during 24 h. International guidelines for the treatment of NF recommend the immediate initiation of antibiotic therapy (<60 minutes). This project aimed to characterize oncologicalhematological patients hospitalized with febrile neutropenia after chemotherapy at the University Hospital of Santa Maria (HUSM), from January 2020 to December 2020. This is a cross-sectional and retrospective observational study. All patients admitted to the oncology sector of HUSM, RS, during the period of this study were included. who had an oncologicalhematological diagnosis (leukemias, lymphomas, multiple myeloma, myeloproliferative syndromes), who were undergoing chemotherapy treatment and over 18 years old. There was a predominance of male patients (55.77%), mean age of 40.60 years, and most were married (57.70%). In terms of the profession, most of them did not fill in this data (42.31%) in the medical records. Regarding education, most had incomplete elementary school (42.01%), and only one patient had completed higher education, but without details of the course. Most patients had no comorbidities (42.31%), and acute myelocytic leukemia (AML- 38.46%) was the most frequent cancer. Two blood culture samples (75.00%) were collected from most patients. Gram positives were the agents with the highest frequency of isolation, 98.08% received empirical antibiotic therapy with at least one drug, and most did not receive empirical antifungals (73.08%). The number of survivors (51.92%) in the period of this study exceeded the number of deaths (48.08%). Final considerations: Immediate recognition of the patient with NF according to risk and adequate treatment with immediate initiation of empirical drug therapy define the patient's survival.